Saturated fatty acids are not off the hook - Dawczynski, Christine; Kleber, Marcus E.; März, Winfried (Nutrition, metabolism and cardiovascular diseases, 2015)
A recent meta-analysis by Chowdhury et al. (2014) has disclaimed the association between coronary artery diseases and either circulating blood levels or the intake of total saturated fatty acids (SFA). Scrutiny revealed that two of the eight studies included in the meta-analysis focused on the proportion of pentadecanoic acid (C15:0) and heptadecanoic acid (C17:0) and their impact on cardiovascular disease (CVD) risk. These odd-chain fatty acids are markers for milk or ruminant fat intake. Both studies indicated inverse associations between milk-fat intake and first-ever myocardial infarction. Neither of the two studies described the association between total circulating blood SFA on coronary outcomes. In contrast to the cardioprotective effects of dairy consumption, we expected that an elevated intake of palmitic acid (C16:0) and stearic acid (C18:0) de novo may raise CVD risk. Thus, it is of particular importance to differentiate the effects of individual circulating SFA on cardiovascular outcomes. Excluding the studies that evaluated the association of fatty acids from milk fat and cardiovascular outcomes revealed a positive association of total SFA blood levels and coronary outcome (RR 1.21, CI 1.04-1.40). Therefore, results obtained from studies of C15:0 and C17:0 cannot be mixed with results from studies of other SFA because of the opposite physiological effects of regular consumption of foods rich in C16:0 and C18:0 compared to high intake of milk or ruminant fat. In our opinion, it is vital to analyze the impact of individual SFA on CVD incidence in order to draw prudent conclusions.